Feminist science and epistemologies: Key issues central to GENNOVATE's research program - Feldman, Shelley (International Maize and Wheat Improvement Center, 2018)
This methodological brief offers a window into GENNOVATE’s innovative collaborative research initiative to promote gender equality in agricultural and natural resource management. It addresses questions such as 1) Why is it important to distinguish among epistemology, methodology, and methods?; 2) What is feminist epistemology?; 3) What can researchers of gender, agriculture, and innovation learn from engaging the contributions of feminist epistemology?; and 4) How has GENNOVATE integrated lessons from feminist methods and feminist epistemics about gender relations, agricultural change, and innovation?